Strategic Human Resource Development: Enhancing Employee Skill for Organizational Growth - Syaefullah, Muhammad; Aswan, Mukhamad Kholil (Journal of Business Management and Economic Development, 2025)
This paper aims to explore the role of Strategic Human Resource Development (SHRD) in enhancing employee skills and fostering organizational growth at the Glawan Village Government, Pabelan District, Semarang Regency. The study adopts a qualitative research approach to investigate how the Glawan Village Government implements SHRD practices and their impact on employee performance and public service outcomes. Semi-structured interviews were conducted with village officials, section heads, and staff from various departments in the Glawan Village Government, using a purposive sampling method to select participants with relevant experience in SHRD. The findings reveal that aligning SHRD practices with the organizational goals of the Glawan Village Government is crucial for achieving long-term success, as organizations that integrate employee development initiatives into their strategic plans experience improved innovation, productivity, and employee retention. Additionally, technical and managerial skills were found to be prioritized, reflecting the growing demand for competencies necessary to navigate the constantly changing demands of public services in the digital era. However, challenges were identified by the Glawan Village Government that failed to fully integrate SHRD into their strategies, resulting in inconsistent outcomes and missed opportunities for improving public services. The study concludes that SHRD should be viewed not just as a tool for enhancing individual performance but as a strategic lever for driving the broader organizational success of the Glawan Village Government. To stay competitive and achieve sustainable growth, the Glawan Village Government must ensure its employee development programs are visionary and aligned with future community demands.